Psychological adjustment challenges among first-year university students: Crucial link between psychological health and academic success in higher education - Anna Niitembu Hako; Prisca Tautiko Shikongo; Aras Bozkurt (International Journal of Studies in Psychology, 2025)
This study investigates the psychological adjustment challenges faced by first-year students at a selected University in Namibia and their impact on first-year university students’ academic performance. The study aimed to understand first-year university students' psychological adjustment challenges, how those challenges affected their academic performances, and the strategies they employed to overcome them. It employed a mixed-methods approach following a convergent parallel design. Data were collected in two phases. Eighty students (80) were selected in this study. The first composed of 46 (57.5%) secondary phase, 23 (28.7%) upper primary phase, and 11 (13.8%) pre-lower primary phase students, and the second involved 10 (47.6%) secondary, 6 (28.5%) upper primary and 5 (23.8%) pre-lower primary phases. Quantitative and qualitative research techniques involved focus group discussions and an online questionnaire featuring closed and open-ended questions. The qualitative findings indicated that students experienced various psychological and academic challenges, including self-harming behaviours, feelings of depression, anxiety, and stress. The results reported poor concentration, difficulties participating in class discussions, frequent forgetfulness, noticing a decline in academic performance, lacking happiness when attending classes, missing classes, and experiencing memory loss. The thematic results suggested that there were significant influences between psychological adjustment and academic performance among first-year students. These findings implicated that the university management must restructure its operational systems to enhance stability, reliability, and effectiveness. Higher education institutions must be aware of psychological adjustment challenges, which require supporting student well-being, improving overall academic outcomes, and creating a more conducive learning environment.